Investment strategy for 2021: market fluctuations in an uneven recovery - A. A. Gafurov; E. I. Kulikova (Путеводитель предпринимателя, 2021)
The purpose of this article is to study the prospects for investment in 2021, both in Russia and abroad. The task is to analyze the macroeconomic situation and financial markets in the world, as well as different sectors of economies with potentially attractive prospects for recovery and development. The methods used in the article are comparison, analysis and synthesis. As a result of the study, economic sectors, asset classes and issuers are identified that can demonstrate significant growth in 2021.